2006
DOI: 10.1021/bi0519710
|View full text |Cite
|
Sign up to set email alerts
|

ESR Signal of the Iron−Sulfur Center FXand Its Function in the Homodimeric Reaction Center ofHeliobacterium modesticaldum,

Abstract: Electron transfer in the membranes and the type I reaction center (RC) core protein complex isolated from Heliobacterium modesticaldum was studied by optical and ESR spectroscopy. The RC is a homodimer of PshA proteins. In the isolated membranes, illumination at 14 K led to accumulation of a stable ESR signal of the reduced iron-sulfur center F(B)(-) in the presence of dithiothreitol, and an additional 20 min illumination at 230 K induced the spin-interacting F(A)(-)/F(B)(-) signal at 14 K. During illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 61 publications
7
80
0
Order By: Relevance
“…It is known that rapid transfer occurs from the excited state of the primary electron donor, P798, to the primary acceptor, 8 1 -OH-Chl a (A 0 ), but the existence of a secondary quinone acceptor (A 1 ) has not been confirmed (41). PshA exists as a homodimer containing two cysteine residues per subunit that are believed to bind to an F X -like [4Fe-4S] cluster (26,38,41). In addition to pshA, a pshB gene (HM1_1462), which encodes an RC-associated [4Fe-4S]-binding ferredoxin, was confirmed to be present in the H. modesticaldum genome.…”
Section: Vol 190 2008 Complete Genome Of H Modesticaldum 4693mentioning
confidence: 99%
“…It is known that rapid transfer occurs from the excited state of the primary electron donor, P798, to the primary acceptor, 8 1 -OH-Chl a (A 0 ), but the existence of a secondary quinone acceptor (A 1 ) has not been confirmed (41). PshA exists as a homodimer containing two cysteine residues per subunit that are believed to bind to an F X -like [4Fe-4S] cluster (26,38,41). In addition to pshA, a pshB gene (HM1_1462), which encodes an RC-associated [4Fe-4S]-binding ferredoxin, was confirmed to be present in the H. modesticaldum genome.…”
Section: Vol 190 2008 Complete Genome Of H Modesticaldum 4693mentioning
confidence: 99%
“…An F x binding motif was first identified in the RC polypeptide of Heliobacillus mobilis (Liebl et al 1993), and the presence of the F x cluster was later confirmed spectroscopically (Heinnickel et al 2006;Miyamoto et al 2006). There is, however, some controversy as to whether the ground state spin is equal to 1/2 (Miyamoto et al 2006) or 3/2 (Heinnickel et al 2006). Two additional [4Fe-4S] clusters, F A and F B , can be reduced by photo-accumulation and distinguished by low-temperature EPR (Nitschke et al 1990).…”
Section: Introductionmentioning
confidence: 95%
“…A putative quinone-binding site in the PshA polypeptide can be predicted, by comparison with the A 1 sites of PsaA/PsaB, but it is should be more polar, due to the replacement of the Trp that p-stacks with phylloquinone in PS1 (Miyamoto et al 2006;Oh-oka 2007) by Arg. Menaquinone is the sole quinone that was found to exist in the membranes of Heliobacterium chlorum, consisting of *79% MK-9 and *15% MK-8 (Hiraishi 1989).…”
Section: Introductionmentioning
confidence: 99%
“…No low-field resonances that could be attributed to an S = 3/2 ground spin state were observed. Curiously, the spectrum of F X was not observed when the F A and F B clusters were removed (Miyamoto et al 2006). …”
Section: The F X Cluster In Heliobacteriamentioning
confidence: 99%
“…However, SDS-PAGE of a wide variety of purified HbRCs failed to reveal a suitable candidate. Moreover, the EPR and time-resolved optical signals characteristic of the F A and F B clusters were invariably absent in published HbRC preparations (Trost and Blankenship 1989;Fuller et al 1985;van de Meent et al 1990;Miyamoto et al 2006). Further complicating the issue was the absence of an fdx-like gene in or near the photosynthetic gene cluster, a region that contains many of the genes required to synthesize an active HbRC (Xiong et al 1998).…”
Section: Pshbi and Pshbii The Proteins Harboring The F A And F B Clumentioning
confidence: 99%